PERAN ADVOKAT DALAM PERLINDUNGAN KORBAN MELALUI BANTUAN HUKUM: PERSPEKTIF VIKTIMOLOGI - Zahara Ananda; Aufiya Muhammad Syukri Alghiffary (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This research is based on the fact that, in a criminal justice system that tends to be perpetrator-centered, the victim's position remains weak. As a result, the protection and fulfillment of victims' rights are not optimal. Advocates play a crucial role as legal aid providers in this situation to ensure that victims have access to justice. The purpose of this study is to evaluate the function of advocates in protecting victims with legal aid from a victimology perspective. Normative juridical research was conducted using a statutory and conceptual approach. The results show that advocates protect victims' rights, assist them in the legal process, and help them obtain justice and redress. However, due to limited access to legal aid, low public legal awareness, and weak implementation of laws protecting victims, this function does not function properly. From a victimology perspective, the role of advocates is crucial in preventing re-victimization and ensuring that victims receive justice oriented toward redress. Therefore, it is necessary to strengthen the role of advocates through increased access to legal aid and a victim-centered approach to achieve substantive justice.